Detection of Damage in Rail Head by using Safe Method - Teidj, Sara.; Driouach, Abdellah; Khamlichi, Abdellatif (Transactions on Engineering and Computing Sciences, 2017)
The first cause of train derailment incidents is due to the transverse defect which occurs in the railhead. It is typically an open or internal crack developing in a plane which is generally perpendicular to the direction of the rail. The most method used today of rail inspection is based on ultrasound .The Ultrasounds based testing is performed according to the excitation-echo procedure. It is conducted conventionally by using a contact excitation probe that rolls on the rail head or by a contact-less system using laser as excitation and air coupled acoustic sensors for wave reception [1]. In this work, Propagation of guided elastic waves in a rail has been modelled by using the semi-analytical finite element method [2]. We have demonstrated the existence of several frequency windows that can be used to excite propagating modes with high deformation in the railhead.